2019
DOI: 10.1371/journal.pone.0219387
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of chromium by root nodule bacteria Sinorhizobium sp. SAR1

Abstract: The present study aims to address the problem of chromium (Cr) toxicity by providing important insights into the mechanisms involved in its bioremediation. Among the 22 Rhizobium and Sinorhizobium isolates obtained from Sesbania sesban root nodules, Sinorhizobium sp. SAR1 (JX174035.1) tolerated the maximum Cr concentration (1mM) and hence was used for further studies. The excess secretion of extra polymeric substances, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…A similar situation has been observed with root nodule bacterium Sinorhizobium sp. SAR1 that tolerated Cr concentrations up to 1 mM due to the production of exopolymers [ 150 ].…”
Section: Biogenic Chromium Mineralsmentioning
confidence: 99%
“…A similar situation has been observed with root nodule bacterium Sinorhizobium sp. SAR1 that tolerated Cr concentrations up to 1 mM due to the production of exopolymers [ 150 ].…”
Section: Biogenic Chromium Mineralsmentioning
confidence: 99%
“…At higher concentrations, more chromium ions are left unabsorbed in the solution due to the saturation of binding sites [110]. e study done by [142] confirms that an increase in metal concentration, from 100 mg/L to 500 mg/L, led to a decrease in percentage Cr(VI) removal (from 99.88% to 83.69%). But analysis of total Cr showed that uptake capacity of the biosorbent SAR1 increased (6.27 mg/g to 28.95 mg/g) with an increase in Cr(VI) concentration.…”
Section: E Influence Of Initial Metal Ion Concentrationmentioning
confidence: 78%
“…Similarly, Jobby et al [48] suggested that the stretch at 1288, 1238, and 1220 cm −1 could be due to the production of exopolysaccharides by aromatic esters under Cr stress conditions.…”
Section: Ftir Raman Spectroscopy and Tem-edx Analysis On The Rhizobac...mentioning
confidence: 92%
“…Our study is in line with the previous reports demonstrated using Methylococcus capsulatus [57], Escherichia coli K-12 [58], Sinorhizobium sp. [48], and Bacillus sp. M6 [59] for intracellular Cr accumulation.…”
Section: Ftir Raman Spectroscopy and Tem-edx Analysis On The Rhizobac...mentioning
confidence: 99%
See 1 more Smart Citation